Gambaran Efek Sekunder dari Terapi Bekam di Universitas Fort De Kock Bukittinggi - Putri, Lydia Mardison; Dewi, Ratna; Wati, Del Fatma (Universitas Fort De Kock Bukittinggi, 2023)
Background: Cupping is a recommended treatment and is a legacy of the great prophet Muhammad SAW, an ancient cupping treatment that still exists today, and its efficacy has been scientifically proven. And critical success at this point lies in negative pressure. Therefore, it is necessary to carry out this research to look at other phenomena of secondary effects due to negative pressure. Methods: Research with a descriptive analytical approach with a sample size of 200 people, data collection using purposive sampling, data processing, percentage frequency distribution (%). Results: The research results found that from 200 samples, 24 people reported itching on the cupping marks immediately after the cupping was done until the cupping marks disappeared. and no other secondary effects were found such as pain, blisters, stinging, chills and dizziness. Conclusion: It is recommended that health workers who perform cupping use herbal oils which can reduce post-cupping histamine reactions to maintain patient comfort.